Improved symptomatic, functional, and fluoroscopic outcomes following serial “series of three” double-balloon dilation for cricopharyngeus muscle dysfunction - Derrick R. Randall; Lisa M. Evangelista; Maggie A. Kuhn; Peter C. Belafsky (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Cricopharyngeus muscle dysfunction (CPMD) is a common cause of dysphagia. We employ a progressive series of three double-balloon dilations separated by 4–6 weeks between procedures as a primary treatment option. The purpose of this study was to evaluate subjective, functional and objective improvement in swallowing after three serial dilations for CPMD. Methods We retrospectively evaluated patients between June 1, 2014, and June 30, 2016, who underwent a series of three double-balloon dilations for CPMD. Pre- and post-dilation Eating Assessment Tool-10 (EAT-10), Functional Oral Intake Scale (FOIS), pharyngeal constriction ratio, pharyngeal area, and pharyngoesophageal segment (PES) opening were compared. Results Seventeen patients with CPMD underwent serial double-balloon dilation procedures separated by one month. Mean age of the cohort was 73.5 (SD ± 13.3) years, and 53% were female. The mean EAT-10 improved from 24.7 (SD ± 7.8) to 15.9 (SD ± 10.2) [p = 0.0021]. Mean FOIS improved from 5.4 (SD ± 1.4) pre- to 6.3 (SD ± 0.9) post-treatment (p = 0.017). Mean UES opening increased from 1.05 (SD ± 0.34) cm to 1.48 (SD ± 0.41) cm (p = 0.0003) in the anteroposterior fluoroscopic view and from 0.58 (SD ± 0.18) to 0.76 (SD ± 0.30) cm (p = 0.018) in the lateral view. Pharyngeal constriction ratio (PCR), a surrogate measure of pharyngeal strength, improved from 0.49 (SD ± 0.37) to 0.24 (SD ± 0.15) (p = 0.015), however pharyngeal area (PA) was unchanged. Conclusions A progressive series of three double-balloon dilations for cricopharyngeus muscle dysfunction resulted in improved patient reported dysphagia symptom scores and objective fluoroscopic swallowing parameters.